Implementasi Persaudaraan Sosial Sebagai Praktik Baik Bagi Perdamaian Dunia Pascapandemi - Willfridus Demetrius Siga; Duen Sant Duary Ginting; Gabriel Mario Lefaan; Doni Irawan; Paulinus Situmorang (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
This study aims to explore the message of The Document on Human Fraternity for World Peace and Living Together and the document on Fratelli Tutti which is realized through social brotherhood as a good practice for post-pandemic world peace. So far, social brotherhood is considered capable of reducing tensions and conflicts that occur. In particular, during the pandemic, social fraternity is considered important to practice the spirit of solidarity. Each individual is guided and directed towards realizing his potential as a social being and encouraging many parties to fight for post-pandemic social brotherhood. Solidarity must be able to penetrate the barriers of difference such as ethnicity, religion, race, and state. This study uses a qualitative method. The data collection was carried out using a documentary approach that was written descriptively by analyzing autobiographies, documents, issues and cases related to the theme of social brotherhood during the pandemic. The results showed that the values promoted in The Document on Human Fraternity for World Peace and Living Together and the document on Fratelli Tutti were able to reduce global conflicts and stimulate solidarity, not only during the pandemic but also post-pandemic situations.